2014
DOI: 10.1149/2.0011503jes
|View full text |Cite
|
Sign up to set email alerts
|

A Fundamental Stability Study for Amorphous LiLaTiO3Solid Electrolyte

Abstract: In this study, amorphous lithium lanthanum titanate (LLTO) powders were prepared by a sol-gel method with an all alkoxide based route. Results showed that unlike its crystalline counterpart which turns into an electronic conductor in direct contact with lithium metal, amorphous LLTO remains to be an ionic conductor and hence is compatible with lithium metal as solid electrolyte although it also undergoes lithium insertion and the consequent reduction of Ti 4+ to Ti 3+ . This striking difference between crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 35 publications
(41 reference statements)
2
32
0
Order By: Relevance
“…However, the deviation of lithium from this formula could be obtained . Depending on the y value, a series of derived crystal structures of the perovskite could be prepared . However, it is reported that Li x La 0.5 TiO 3 could maintain the same crystal structure in the range 0.37< x <0.595, and the x value in this work is within this range.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…However, the deviation of lithium from this formula could be obtained . Depending on the y value, a series of derived crystal structures of the perovskite could be prepared . However, it is reported that Li x La 0.5 TiO 3 could maintain the same crystal structure in the range 0.37< x <0.595, and the x value in this work is within this range.…”
Section: Resultsmentioning
confidence: 74%
“…Perovskite is a general term for a structural family of CaTiO 3 , which has a general formula of ABO 3 with alkaline rare or earth metal ions in A sites and transition‐metal ions in B sites . A series of Li 3 y La 2/3− y TiO 3 has been synthesized with Li and La occupying the A positions, which exhibited a Li ion conductivity exceeding 10 −3 S cm −1 at room temperature (RT) . The high ion conductivity of perovskite Li 3 y La 2/3− y TiO 3 has aroused the strong interest of researchers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amorphous LLTO is compatible with lithium metal, which makes lithium as anode possible. 9 Although Ti 4+ to Ti 3+ reduction still accompanies lithium insertion into amorphous LLTO, its local atomic disorder is considered to localize the electronic states. Amorphous LLTO thin lm prepared by pulsed laser deposition (PLD) exhibits higher ionic conductivity (8.94 Â 10 À4 S cm À1 ) than the crystalline counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…19 Zheng et al also demonstrated that amorphous LLTO powders by sol-gel synthesis remain ionically conductive in contact with lithium metal even though it undergoes the same lithium insertion and Ti 4+ to Ti 3+ reduction. 8 They hypothesize that this phenomenon is due to local atomic disorder in the amorphous case that localize electronic states.Lastly, amorphous LLTO thin films have a large voltage stability window, which opens a pathway for high-voltage cathode materials, such as LiNi 0.5 Mn 1.5 O 4 (LNMO) spinel. High-voltage cathodes have the potential to greatly improve the energy density of lithium ion batteries, but current liquid electrolytes face stability issues at high voltage due to strong oxidation reactions.…”
mentioning
confidence: 99%